A Bayesian Abstract Economy with a Measure Space of Agents. (27th September 2009) - Patriche, Monica
Abstract : We define the model of an abstract economy with differential (asymmetric) information and a measure space of agents. We generalize N. C. Yannelis's result (2007), considering that each agent is characterised by a random preference correspondence instead of having a random utility function. We establish two different equilibrium existence results.